DETERMINANTS OF GREEN SUPPLY CHAIN MANAGEMENT PRACTICES ON PERFORMANCE OF GAS MANUFACTURING FIRMS IN KENYA - Nyachomba, Judy; Achuora, John (International Journal of Supply Chain and Logistics, 2022)
Purpose: This study aimed to assess the determinants of green supply chain management practices on the performance of gas manufacturing companies in Kenya. Methodology: This research study adopted a descriptive research design approach. The researcher prefers this method because it allows an in-depth study of the subject. There are twenty-eight (28) gas manufacturing firms in Kenya according to the Petroleum Institute of East Africa (PIEA) directory in 2021. The unit of analysis was the individual gas manufacturing firms. The unit of observation was five (5) procurement officers from each of the twenty-eight (28) gas manufacturing firms in Kenya. The total number of respondents was one hundred and forty (140). The study in its data collection used questionnaires. After data collection, quantitative data was coded using Statistical Package for Social Science (SPSS) version 20. Data were analyzed through descriptive statistical methods such as means, standard deviation, frequencies, and percentages. Inferential analyses were used in relation to correlation analysis and regression analysis to test the relationship between the four explanatory variables and the explained variable. Results were presented using tables, graphs, and charts Results and conclusion: The response rate of the study was 85%. The independent variables reported-value of .775 indicating that there isa perfect relationship between the dependent variable and independent variables. R square value of 0.6 means that 60% of the corresponding variation in performance of gas manufacturing firms can be explained or predicted by green product design, green distribution, green warehousing and reverse logistics, which indicated that the model fitted the study data. The findings of the study indicated that green product design, green distribution, green warehousing,g, and reverse logistics have a positive relationship with performance in gas manufacturing firms Policy recommendation: The study recommended that gas manufacturing firms should embrace green supply chain management practices so as to improve performance and furtherresearchs should be carried out in other institutions to find out if the same results can be obtained.